Responses of floodplain birds to high‐amplitude precipitation fluctuations over two decades. (11th March 2022) - Reid, Tim; Lada, Hania; Selwood, Katherine E.; Horrocks, Gregory F. B.; Thomson, James R.; Mac Nally, Ralph
Abstract: Globally, high‐amplitude variation in weather ( e.g . precipitation) is increasing in frequency and magnitude. This appears to be so for the southern Murray‐Darling Basin, Australia, where droughts of unprecedented (in the instrumental record, extending back to the mid‐1800s) depth and duration (1997–first half of 2010; second half of 2012–) are being punctuated by extreme wet periods, albeit of shorter duration ('Big Wet', second half of 2010–first half of 2012). We have previously reported on the responses of floodplain‐forest birds to the cessation of the longest recorded drought ('Big Dry', 1997–first half of 2010), but we found little evidence of a rebound, at least shortly after the Big Wet. However, we reasoned that there may have been insufficient time for the birds to have responded in that short time, so we repeated the survey program 5 years after the end of the Big Wet (2017). Bird occurrences, reproductive activity and success were substantially greater compared with late in the Big Dry (2009) than they had been soon after the Big Wet (2013). However, bird occurrences still fell well below measurements in the early‐Big Dry (1998), so that the avifauna appears to be in decline, most probably because the length of drought periods far exceeds that of wet periods giving the birds too little time to recover fully.